2019
DOI: 10.3390/vetsci6040103
|View full text |Cite
|
Sign up to set email alerts
|

Case Reports for Topical Treatment of Corneal Ulcers with a New Matrix Therapy Agent or RGTA® in Dogs

Abstract: Superficial corneal ulcers that fail to heal within a normal time period and are refractory to conventional therapy in dogs are common in veterinary practice. Different etiologies can lead to this result, including spontaneous chronic corneal epithelial defects (SCCEDs) and ulcerative keratitis associated with bullous keratopathy. Thus, there is an urgent need to find new therapeutic approaches such as matrix therapy replacement. To determine the efficacy of a new ophthalmic treatment (Clerapliq ® ) for SCCEDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The only report on the use of RGTAs in the dog is a case series of 11 dogs treated for ulcerative keratitis associated with bullous keratopathy [ 62 ]. Martinez et al [ 62 ] found that the corneas with recurrences of the ulcers were resolved predominantly by using RGTAs and that they can be considered a successful adjunctive therapy in the management of superficial ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The only report on the use of RGTAs in the dog is a case series of 11 dogs treated for ulcerative keratitis associated with bullous keratopathy [ 62 ]. Martinez et al [ 62 ] found that the corneas with recurrences of the ulcers were resolved predominantly by using RGTAs and that they can be considered a successful adjunctive therapy in the management of superficial ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an urgent need to find new therapeutic approaches for CU, has gained the attention of veterinary clinics. Alternative treatments such as platelet-rich plasma [12], amniotic membrane graft [13], matrix regenerating agents [14,15] have been reported. Recently MSCs has been used as an alternative for CU in humans, with outstanding outcomes [16].…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Matrix regenerating agents have also been successfully used in dogs for PED, but these are not yet reported in horses. 39 Serum is a biological tear substitute. 2,40 This is known to provide lubrication, growth factors and cytokines for the surface of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to improve tear film osmolarity, promote homeostasis and tear film retention, improving clinical signs by lubricating and lipid replacement 36–38 . Matrix regenerating agents have also been successfully used in dogs for PED, but these are not yet reported in horses 39 …”
Section: Discussionmentioning
confidence: 99%